Internally versus externally trained residents and fellows hired as attendings at a large integrated healthcare system: a 20-year retrospective study - Stephen M. Wertheimer; Jerad A. Harris; J. Craig Collins; Nancy H. Spiegel; Gary W. Chien (BMC, 2023)
Abstract Background There remains a question of whether graduates trained internally are different than those trained elsewhere. We examine the difference between physicians trained within our Graduate Medical Education (GME) programs versus physicians trained elsewhere. Our large integrated healthcare system is unique in addressing this objective due to its large physician labor hiring needs across different specialties of GME graduates. Methods A retrospective review was performed from Jan 2000 to August 2020 of Kaiser Permanente Southern California (KPSC) physicians hired: KPSC GME trained versus non-KPSC GME trained. We examined five variables: retention, leadership (current or historical), physician relations cases, member appraisal of physician and provider services survey (MAPPS) scores, and rate of board certification. Chi-square test of proportions was used for comparison, p < 0.05 was significant. Results From Jan 2000 to August 2020, 2940 residents and fellows graduated from KPSC GME programs, of which 1127 (38%) were hired on at KPSC as full time attendings. Across all five metrics (Retention 82% vs 76% (p =  < 0.01), Leadership [current 13% vs 10% (p =  < 0.01)or historical 17% vs 14% (p = 0.01)], Physician Relations 23% vs 26% (p = 0.04), MAPPS 75% vs 69% (p =  < 0.01), and Board Certification 81% vs 74% (p =  < 0.01)), KPSC outperformed non-KPSC GME-trained physicians to a statistically significant degree. Conclusions We have shown that an internally sponsored GME program can represent an opportunity for recruitment of physicians that may have higher retention rates, higher probability of being physician leaders, decreased likelihood of physician relations issues, improved patient satisfaction, and increased rates of board certification.